2017
DOI: 10.1186/s12943-017-0666-z
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression analysis at the individual level reveals a lncRNA prognostic signature for lung adenocarcinoma

Abstract: BackgroundDeregulations of long non-coding RNAs (lncRNAs) have been implicated in cancer initiation and progression. Current methods can only capture differential expression of lncRNAs at the population level and ignore the heterogeneous expression of lncRNAs in individual patients.MethodsWe propose a method (LncRIndiv) to identify differentially expressed (DE) lncRNAs in individual cancer patients by exploiting the disrupted ordering of expression levels of lncRNAs in each disease sample in comparison with st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
100
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(108 citation statements)
references
References 43 publications
(59 reference statements)
4
100
0
1
Order By: Relevance
“…Previous studies analyzed the gene expression profiles of LUAD patient samples to identify prognostic biomarkers and classified the lung cancer subtypes based on gene expression . RNA‐Seq data show that some long noncoding RNAs (lncRNAs) such as C1orf132 and TMPO‐AS1 are associated with increased risk of LUAD and show potential as prognostic biomarkers . Studies based on single nucleotide polymorphism (SNP) arrays and targeted sequencing or whole‐genome/exome sequencing of protein‐coding genes (PCGs) have identified somatic mutations, focal amplifications or copy number alterations in many oncogenes and tumor suppressor genes such as RIT1 and MGA in LUAD patients .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies analyzed the gene expression profiles of LUAD patient samples to identify prognostic biomarkers and classified the lung cancer subtypes based on gene expression . RNA‐Seq data show that some long noncoding RNAs (lncRNAs) such as C1orf132 and TMPO‐AS1 are associated with increased risk of LUAD and show potential as prognostic biomarkers . Studies based on single nucleotide polymorphism (SNP) arrays and targeted sequencing or whole‐genome/exome sequencing of protein‐coding genes (PCGs) have identified somatic mutations, focal amplifications or copy number alterations in many oncogenes and tumor suppressor genes such as RIT1 and MGA in LUAD patients .…”
Section: Introductionmentioning
confidence: 99%
“…7,8 RNA-Seq data show that some long noncoding RNAs (lncRNAs) such as C1orf132 and TMPO-AS1 are associated with increased risk of LUAD and show potential as prognostic biomarkers. [9][10][11][12] Studies based on single nucleotide polymorphism (SNP) arrays and targeted sequencing or wholegenome/exome sequencing of protein-coding genes (PCGs) have identified somatic mutations, focal amplifications or copy number alterations in many oncogenes and tumor suppressor genes such as RIT1 and MGA in LUAD patients. 13,14 In human cancers, copy number alterations (CNAs) are the most common type of genetic alterations; they influence activation of oncogenes and repression of tumor suppressor genes.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence shows that lncRNAs play a critical role in cancer biology. Dysregulation of lncRNAs often serves as an independent predictor for poor prognosis of cancer patients . Our group has previously reported that circulating lncRNAs act as potential novel biomarkers for diagnosis and prognosis of non‐small cell lung cancer .…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulation of lncRNAs often serves as an independent predictor for poor prognosis of cancer patients. [5][6][7][8][9] Our group has previously reported that circulating lncRNAs act as potential novel biomarkers for diagnosis and prognosis of non-small cell lung cancer. 10 Several recent studies have focused on the involvement of lncRNAs in tumor metastasis because these lncRNAs have shown great promise in the discovery of new biomarkers for predicting prognosis in individual patients.…”
Section: Introductionmentioning
confidence: 99%
“…TMPO-AS1 could also affect the prognosis of patients with lung adenocarcinoma through regulating cell cycle and cell adhesion. 6 With regard to cervical cancer, Liu et al 7 showed that TMPO-AS1 was highly expressed in the cervical cancer tissues when compared with the adjacent tissues according to chip analysis. However, the expression of TMPO-AS1 in cervical cancer cells and its exact role in cervical cancer remain unclear.…”
Section: Introductionmentioning
confidence: 99%